A comparative assessment of fixation strength of anchors in spongy bones - Pazdnikov, Roman; Tyazhelov, Olexiy; Karpinsky, Mykhaylo; Karpinska, Olena; Subbota, Igor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
Fixation strength of different kinds of anchors and transosseous fixation with help of ligation sutures was comparatively analysed. It was experimentally proved that stabilization with help of screw-in anchors had a higher stiffness of fixing than transosseous sutures.